Practical Synthesis of Chiral N-Heterocyclic Carbene Triazolium Salts Containing a Hydroxy Functional Handle - Dhayalan, Vasudevan; Mal, Kanchan; Milo, Anat (Synthesis, 2019)
A library of functionalized chiral pyrrolidine-based N-heterocyclic carbene triazolium salts containing a hydroxy handle is prepared from readily accessible chiral (S)-pyroglutamic acid in eight steps. This improved synthetic protocol affords increased yields for known structures and 18 new NHCs are prepared by this method. The presence of a hydroxy handle offers potential for further functionalization and for non-covalent control over catalytic reactions in which the NHCs can serve as organocatalysts or ligands for organometallic catalysis.
Keywords: N-heterocyclic carbenes; triazolium salts; organocatalysis; organomagnesium reagents; arylhydrazines; benzyl alcohol; protecting groups; desilylation